A methodology for estimating the parameters of a gamma raindrop size distribution model from polarimetric radar data: application to a squall-line event from the TRMM/Brazil campaign - Bringi, V. N., author; Chandrasekar, V., author; Huang, Gwo-Jong, author; Gorgucci, E., author; American Meteorological Society, publisher (Colorado State University. Libraries, 2002)
A methodology is proposed for estimating the parameters of a gamma raindrop size distribution model from radar measurements of Zh, Zdr, and Kdp at S band. Previously developed algorithms by Gorgucci et al. are extended to cover low rain-rate events where both Zdr and Kdp are noisy. Polarimetric data from the S band Dual-Polarization Doppler Radar (S-Pol) during the Tropical Rainfall Measuring Mission (TRMM)/Brazil campaign are analyzed; specifically, the gamma parameters are retrieved for samples of convective and trailing stratiform rain during the 15 February 1999 squall-line event. Histograms of Nw and Do are retrieved from radar for each rain type and compared with related statistics reported in the literature. The functional behavior of Nw and Do versus rain rate retrieved from radar is compared against samples of 2D-video and RD-69 disdrometer data obtained during the campaign. The time variation of Nw, Do, and μ averaged over a 5 km × 5 km area (within which a network of gauges and a profiler were situated) is shown to illustrate temporal changes associated with the gamma parameters as the squall line passed over the network. The gauge-derived areal rainfall over the network is compared against radar using the areal ϕdp method, and the concept of an effective slope of a linear axis ratio versus diameter model is shown to significantly reduce the bias in radar-derived rainfall accumulation.